Screening of ADHD symptoms in primary school students and investigation of parental awareness of ADHD and its influencing factors: A cross-sectional study - Li, Hong-Hua; Wang, Tian-Tian; Dong, Han-Yu; Liu, Ya-Qin; Jia, Fei-Yong (Frontiers in Psychology, 2022)
Objective The present study aimed to compare the differences in positive screening rates of ADHD symptoms between parents and teachers in the same sample of primary school students. Concurrently, parental awareness and information sources of ADHD were investigated, and possible relevant factors affecting parental awareness and their influence on positive screening rate of ADHD were analyzed. Methods A cross-sectional study was conducted in Changchun, China, between September 2020 and January 2021. Parents of 1,118 primary school students and 24 head teachers were recruited in the survey. Data were collected through a structured self-administered questionnaire. It consisted of socio-demographic characteristics, ADHD symptom screening questionnaire, parental awareness, and information sources of ADHD. Results Among the 1,118 primary school students, 30 (2.7%) and 60 (5.4%) students were positive for SNAP-IV screening in the parent version and teacher version, respectively. Parents had lower positive screening rates for ADHD symptoms than teachers. Relationship with children (mother, OR = 1.552, 95% CI = 1.104–2.180), bachelor degree or above of parents (OR = 1.526, 95% CI = 1.054–2.210), children’s sex (Girl, OR = 1.442, 95% CI = 1.093–1.904) and age (OR = 1.344, 95% CI = 1.030–1.754), children’s grade (grade 2, OR = 0.522, 95% CI = 0.310–0.878; grade 3, OR = 0.388, 95% CI = 0.185–0.782), information sources of ADHD (medical staff, OR = 1.494, 95% CI = 1.108–2.015; family/relative/friend, OR = 1.547, 95% CI = 1.148–2.083; TV/Internet, OR = 3.200, 95% CI = 2.270–4.510) were the factors related to the parental awareness of ADHD. Conclusion Parents and teachers of primary school students recognize ADHD symptoms differently. The positive screening rate of ADHD among teachers was significantly higher than that of parents. Relationship with children, educational level of parents, children’s sex, age, and grade, and information sources of ADHD are the relevant factors affecting parental awareness of ADHD. More efforts should be made to disseminate ADHD knowledge through mass media, and medical staff. Fathers, parents with low educational level, and parents of grade 2 and 3 pupils should be encouraged to acquire more knowledge on ADHD to improve the early recognition rate of ADHD symptoms.